Surface enhanced raman scattering dependence on chain-length of 1-alkanethiols on gold and silver nanoparticles - Shumbula, Ndivhuwo Prince (My University, 2018)
Surface enhanced Raman spectroscopy (SERS) is a surface sensitive technique through which the Raman signal of molecules adsorbed on a metallic surface is enhanced. It is a molecular vibrational technique which has evolved from the classic Raman spectroscopy in early 1970s. This technique is widely used for identification of solid, liquid and gas analytes. It also enables a sensitive detection of single molecule and also provides its distinguished chemical fingerprints. This technique has the ability to improve the Raman cross section by orders of up to 1015. The enhancement of local magnetic field due to localised surface plasmon resonance (SPR) is greatly dependent on SERS substrates (i.e. metal nanoparticles) used and the molecule (Raman reporter) attached to the substrate. In the current project, we report on the effect that the chain-length of 1-alkanethiol functionalized on gold and silver nanoparticles (AuNPs and AgNPs) has on the Raman scattering enhancement. AuNPs and AgNPs were synthesized by the reduction of chloroauric acid and silver nitrate respectively, using tri-sodium citrate as a reducing agent. Citrate capped nanoparticles were obtained and further functionalized with 1-alkanethiols of different chain-lengths, i.e. pentanethiol (PT), decanethiol (DT), dodecanethiol (DDT), and pentadecanethiol (PDT). The 1-alkanethiols were chosen as Raman reporters because they are able to form self-assembled monolayer (SAM) systems on the surface of metals, thus influencing their stability. The optical properties of both functionalized (SAMs) and unfunctionalized AuNPs and AgNPs were studied using ultraviolet-visible (UV-Vis) spectroscopy. A red shift of the SPR bands of AuNPs and AgNPs prior to functionalization with 1-alkanethiols was observed from the UV-Vis spectra. AuNPs and AgNPs which were monodispersed and spherical-like morphology with the average diameters of 14 and 25 nm respectively were obtained as was evidenced from the transmission electron microscopic (TEM) analysis. The obtained negative zeta potential indicated negatively charged surfaces for both AuNPs and AgNPs. AuNPs were more stable and well dispersed in the colloidal solution as compared to AgNPs since they possessed a strong negative zeta potential. The effect of chain-length on Raman scattering was evaluated using Raman spectroscopy and the enhancement factor (EF) was calculated from the intensities of symmetric stretch vibrations of C-H observed in the region of about 2900 to 3000 cm-1 in all SERS spectra. SERS spectra for all 1-alkanethiols (Raman reporters) showed more intense characteristic peaks as compared to their classical Raman spectra. Some vibrational modes which were not observed in classical Raman spectra where observed from the SERS spectra. The shorter chain-length PT possessed a higher enhancement factor (EF) of the Raman cross-section as compared to the longer chain-lengths 1-alkanethiols. DFT and Molecular Dynamic studies were done to establish the influence of the chain length on the EF. The geometry of the RR adsorbed on the metal surface as well as the position in which the RR was adsorbed on the metal surface was found to influence the charge density transfer hence the SERS spectra obtained. From the calculations, it was evident that the adsorption of the RRs on both Ag and Au metals resulted on an enhanced Raman spectra however other factors influenced the observed EF trend.
A dissertation submitted for the partial fulfillment of the requirements for the degree of Master of Science in Chemistry Faculty of Science University of the Witwatersrand
Keywords: Raman spectroscopy; Nanoparticles